Persepsi Orang Tua terhadap Faktor-Faktor yang Mempengaruhi Perilaku Moral Anak Usia 5-6 Tahun di TK FKIP Universitas Riau - Ester Teti Teresa Tambunan; Daviq Chairilsyah; Enda Puspitasari (Departement of Mathematics Education, 2024)
This study aims to understand parents' perceptions of the factors influencing the moral behavior of children aged 4-5 years at TK FKIP Universitas Riau. Observations indicate that children tend to exhibit a lack of moral behavior, such as reluctance to greet elders, unwillingness to share food, not praying before and after meals, not eating calmly, and not respecting their peers. This descriptive study employs a quantitative approach, using Suharsimi Arikunto's (2003) three-ranking grouping analysis to determine the accuracy of the issues. The sample consists of 40 parents, specifically mothers, of children attending TK FKIP Universitas Riau. Data analysis results show that parents' perceptions of the factors influencing the moral behavior of children are categorized as fairly good. Parents are considered the main factor in the development of children's moral behavior, given that the time children spend with parents is longer compared to time spent with teachers at school. In conclusion, the role of parents is crucial in developing children's moral behavior.